Development of an electrostatic spray setup for water-based PEDOT : PSS thin film fabrication for organic solar cells application. - Lim, Kong Hooi. (2009)
Currently, energy had become a big issue to the human race. The need for energy is ever increasing but the source of energy on the earth is always limited. Therefore, there had been an increasing development in other sources of energy, for example the renewable energy like solar energy. Even though the development of solar cell had made it more reliable, most of it is silicon base. It is not recyclable and thus will produce pollution during disposal. For the organic base solar cell, most of it uses organic solvent with are not environmental friendly. Therefore, it is the purpose of this project to find out the feasibility of a water base route to fabricate a PEDOT:PSS thin film that can be apply to solar cell using electrospray. Electrospray system is a relatively cheap and easy to handle apparatus. Therefore, any success in this project may signify a new era in the technology of fabrication of a more environmental friendly solar cell.